Thank you for the opportunity to help you with your question!
Dividing both sides of the initial equation by 3x and multiplying both sides by dx gives the equation:
dy = (sqrt(x^2-25)/(3x))dx
This equation can be integrated leaving the equation:
y = (1/9)(sqrt(x^2-25)^(3/2)) + C.
Plugging in the point (5,3) means C = 3 so the final answer is:
y = (1/9)(sqrt(x^2-25)^(3/2)) + 3
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?